2017
DOI: 10.1111/epi.13678
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation: Surgical technique of implantation and revision and related morbidity

Abstract: SUMMARYIndications for vagus nerve stimulation (VNS) therapy include focal, multifocal epilepsy, drop attacks (tonic/atonic seizures), Lennox-Gastaut syndrome, tuberous sclerosis complex (TSC)-related multifocal epilepsy, and unsuccessful resective surgery. Surgical outcome is about 50-60% for seizures control, and may also improve mood, cognition, and memory. On this basis, VNS has also been proposed for the treatment of major depression and Alzheimer's' disease. The vagus nerve stimulator must be implanted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
143
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(171 citation statements)
references
References 52 publications
3
143
0
6
Order By: Relevance
“…Other complications include vagus nerve injury, delayed wound healing, dyspnoea (from left vocal cord paralysis) and cough. Transient hoarseness (from stimulation of the recurrent laryngeal nerve) can occur in around 66% of patients but is transient during periods of stimulation . These side effects, albeit rarer when in the hands of experienced practitioners, must be considered alongside any benefit the device is thought to give to the patient.…”
Section: Therapeutic Modulation Of Parasympathetic Tonementioning
confidence: 85%
“…Other complications include vagus nerve injury, delayed wound healing, dyspnoea (from left vocal cord paralysis) and cough. Transient hoarseness (from stimulation of the recurrent laryngeal nerve) can occur in around 66% of patients but is transient during periods of stimulation . These side effects, albeit rarer when in the hands of experienced practitioners, must be considered alongside any benefit the device is thought to give to the patient.…”
Section: Therapeutic Modulation Of Parasympathetic Tonementioning
confidence: 85%
“…In these conditions the cervical vagus nerve is chronically stimulated through an implanted device (Giordano et al. ) and the therapeutic effects are thought to be mediated through afferent signaling to the central nervous system (Groves and Brown ; Krahl and Clark ). However, in a previous study (Meyers et al.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, VNS is FDA-approved for the treatment of therapy-refractory epilepsy (Nune et al 2015) and major depression (Cristancho et al 2011). In these conditions the cervical vagus nerve is chronically stimulated through an implanted device (Giordano et al 2017) and the therapeutic effects are thought to be mediated through afferent signaling to the central nervous system (Groves and Brown 2005;Krahl and Clark 2012). However, in a previous study (Meyers et al 2016), we demonstrated that afferent signaling evoked by cervical VNS inhibits insulin secretion and markedly increases resting blood glucose levels in anesthetized rats, raising the question if patients treated with cervical VNS are at risk of developing glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Our experience shows that the close collaboration between ENT surgeons and epileptologists, able to combine the anatomical knowledge of the cervical region and endoscopic access to the side effects site with the electrophysiological knowledge of the VNS, is essential for the reaching of this goal. Surgery for complete removal or revision and replacement of the device should be regarded as an extreme measure, to be considered only in cases of device malfunction (4%‐16.8%), failure of VNS therapy, intolerable side effects, or patients' specific requests …”
Section: Discussionmentioning
confidence: 99%
“…Early complications consist in intraoperative bradycardia (1/1000 cases), infections (3%‐8%), and VN injury. Late complications consist mainly in laryngeal dysfunction with hoarseness, dyspnoea and cough, usually related to the frequency of stimulation, vocal fold palsy, laryngopharyngeal reflux, and obstructive sleep breathing disorders . While most of these alterations have been related to the variation of vocal cord movements during stimulation or to the orthodromic effect of VN stimulation, no study associated, at present, abnormal laryngopharyngeal movements with dysphagia symptoms, which are nevertheless well‐known in VNS patients.…”
Section: Introductionmentioning
confidence: 99%